The Effectiveness of Course Review Horay Method on Social Sciences Learning Achievement of Visually Impaired Students - Hermawan Hermawan; Kresna Hertantio Putro; Sugini Sugini (Journal of ICSAR, 2018)
This study aims to determine the effectiveness of the Course Review Horay (CRH) method of the social sciences learning achievement of 5th-grade students with visual impairment of SLB A YKAB Surakarta. This research is an experimental research of pre-experimental type research in the form of one group pretest-posttest design. The population in this study are 4 5th grade students of visual impairment in SLB A YKAB Surakarta. Data were analyzed by using non-parametric analysis Wilcoxon Signed Rank Test (Wilcoxon Signed Rank Test). The results showed that the average value before using CRH method was 10, while the mean value after using the CRH method was 40. Based on the results of the study, it can be concluded that the Course Review Horay method is effective to improve the social sciences learning achievement 5th-grade students with visual impairment SLB A YKAB Surakarta.